Collusive Tax Evasion and Social Norms - Martin Abraham; Kerstin Lorek; Friedemann Richter; Matthias Wrede (Center for Economic Studies and ifo Institute (CESifo), 2015)
Although collusive tax evasion by buyers and sellers of commodities and also by employers and employees is widespread all over the world, it has rarely been analyzed in the tax evasion literature. To fill this gap and to compare collusive tax evasion with independent tax evasion, this paper develops a simple non-cooperative game-theoretic model and confirms the model's predictions in a laboratory experiment. Because collusive tax evasion involves social interaction, this paper focuses on the effect of social norms and theoretically and empirically demonstrates that the tax compliance norm has a stronger negative effect on the magnitude of collusive tax evasion than on independent tax evasion. The reason for this result is that in a collusive tax evasion game with multiple equilibria social norms act as an equilibrium selection device, whereas social norms need to be internalized to change the behavior of taxpayers who evade taxes unobservedly.
Keywords: H26; A13; 330; collusive tax evasion; third-party reporting; social norms